Analisis Motivasi Kerja Pegawai - Didin Mushlihuddin; Anton Tirta Komara; Boy Suzanto (Majalah Bisnis & IPTEK, 2019)
This study aims to analyze employee work motivation. Work motivation analyzed is based on Theory Mc Cleland, which consists of 3 (three) dimensions, namely the need for achievement, the need for affiliation, and the need for power. The research method used is descriptive. The sample used is an employee at a government agency in Bandung Regency. Data analysis techniques using descriptive analysis. The results of the study illustrate that employee motivation is sufficient.